What critical thinking skills and dispositions do new graduates need for professional life? Views from Portuguese employers in different fields - Cruz, G. (2020)
Even though Critical Thinking (CT) is an important goal for higher education institutions and labour market professionals, studies dealing with employers’ perceptions on CT meaning and envisioning in the workplace are scarce. Intended to tackle this gap, the current study provides an overview of the need for and practical application of CT in the workplace from the employers’ views. Adopting a qualitative research methodology, five focus group interviews were carried out, enrolling 28 representatives of different Portuguese Non-Governmental Organizations (NGO), public and private companies, in four different professional fields: Biomedicine, STEM (Sciences, Technology, Engineering and Mathematics), Social Sciences, and Humanities. Using Facione’s framework for data analysis, results suggest that CT is broadly recognized by employers as a set of interdependent skills and dispositions that are needed in new graduates, presenting slight differences in their practical application across professional fields. This paper also discusses and outlines implications to support universities in the promotion of students’ CT skills and dispositions.